2022
DOI: 10.1136/ard-2022-223365
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of synthetic and biological DMARDs: a systematic literature review informing the 2022 update of the EULAR recommendations for the management of rheumatoid arthritis

Abstract: ObjectivesTo update the evidence on efficacy of DMARDs (disease-modifying antirheumatic drugs) and inform the taskforce of the 2022 update of the European Alliance of Associations for Rheumatology (EULAR) recommendations for management of rheumatoid arthritis (RA).MethodsThis systematic literature review (SLR) investigated the efficacy of conventional synthetic (cs), biological (b), biosimilar and targeted synthetic (ts)DMARDs in patients with RA. Medline, EMBASE, Cochrane CENTRAL and Web of Science were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Inability to discontinue GCs due to persistently active disease suggests that the ongoing DMARD therapy is not sufficiently effective and needs to be amended, in line with the treat-to-target approach that is also strongly recommended by the EULAR Task Force. The SLR on efficacy 16 confirmed the excellent efficacy of a combination of csDMARDs with GC as for instance evidenced in the NORD-STAR trial: non-inferiority was shown for csDMARDs+GC versus certolizumab+MTX and tocili-zumab+MTX while abatacept+MTX was statistically superior, 40 but in this respect it is important to refer to two other trials, namely AMPLE, comparing abatacept with adalimumab 41 and EXXELERATE, comparing certolizumab pegol with adalimumab, 42 with superimposable results in both studies. Thus, also NORD-STAR revealed clinical similarity between csDMARD+GC therapy and any bDMARD+MTX treatment, with high rates of stringent remission by CDAI at 24 weeks (>40%) for all these therapies.…”
Section: Recommendationsupporting
confidence: 53%
See 2 more Smart Citations
“…Inability to discontinue GCs due to persistently active disease suggests that the ongoing DMARD therapy is not sufficiently effective and needs to be amended, in line with the treat-to-target approach that is also strongly recommended by the EULAR Task Force. The SLR on efficacy 16 confirmed the excellent efficacy of a combination of csDMARDs with GC as for instance evidenced in the NORD-STAR trial: non-inferiority was shown for csDMARDs+GC versus certolizumab+MTX and tocili-zumab+MTX while abatacept+MTX was statistically superior, 40 but in this respect it is important to refer to two other trials, namely AMPLE, comparing abatacept with adalimumab 41 and EXXELERATE, comparing certolizumab pegol with adalimumab, 42 with superimposable results in both studies. Thus, also NORD-STAR revealed clinical similarity between csDMARD+GC therapy and any bDMARD+MTX treatment, with high rates of stringent remission by CDAI at 24 weeks (>40%) for all these therapies.…”
Section: Recommendationsupporting
confidence: 53%
“…The results of the SLRs will not be presented here in detail but are presented in respective parallel publications. [14][15][16] However, if pertinent for the explanation of the results, parts of these data will be mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the evidence that informs this choice is, even on a population level, limited. [1][2][3] While superior/non-inferior efficacy of one treatment over another can be demonstrated in relatively small studies with limited follow-up, many safety concerns require larger studies and longer follow-up times for differences to become clear, even when the induction time for a given safety event itself is not an issue. This is recognised by the regulatory framework where data from pivotal randomised controlled trials (RCTs) are usually considered sufficient for demonstrating the efficacy and non-toxicity of the drug, but postapproval safety studies (PASS) are required for several years to evaluate drugassociated risks.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The current issue of ARD focuses on the advances that were brought about by several of EULAR’s international Task Forces. To this end, an update of the EULAR recommendations for the management of RA,6 accompanied by three systematic literature researches,7–9 is now presented. These recommendations account for the most recent developments in the field and do not back away from thoroughly addressing challenges that have occurred in the recent past 10 11.…”
mentioning
confidence: 99%